Factors Affecting Learning Achievement: Learning Discipline and Self-regulation at MTs Wachid Hasyim Surabaya - Maharani, Lely; Darmawan, Didit (Universitas Islam Sultan Agung, 2024)
This one indicator of educational success is student learning achievement which is influenced by various factors, including learning discipline and self-regulation. This study intends to explore the influence of learning discipline and self-regulation on student learning achievement at MTs Wachid Hasyim Surabaya. This research will involve quantitative data analysis using questionnaires as data collection tools. By focusing on study discipline and self-regulation, it involves 57 seventh grade students. The data analysis technique employed in this research is multiple linear regression. The results of the analysis show that learning discipline variable obtained a significance level of 0.004, while the self-regulation variable showed a significance value of 0.000. This implies that, each variable has a separate and significant influence on the variation of learning achievement. These findings illustrate that learning discipline and self-regulation make a significant contribution to student learning achievement. Students with high levels of learning discipline tend to achieve better learning outcomes. Moreover, students who can self-regulate, including in time management and learning strategies, are more likely to attain academic success.